(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the article, various methodic recommendations are provided, which correspond to various stages of education. They give attention not only to linguistic form of expression, but to informal form. Interactive forms of teaching are proposed for speaking. Education is very important for our lives. The importance of native language knowledge, day by day is reaching the great top because of the unity development between different nations and countries that leads to fruitful relationships. The formation of linguistic and communicative competences is of equal importance when teaching a native language. With the growing requirements to the quality of specialists training, these competences have become essential qualifications. Use of innovational technologies in studying native languages gives pupils an opportunity of diverse means foundation of relation in native language.